Surface Modification with NGF-Loaded Chitosan/Heparin Nanoparticles for Improving Biocompatibility of Cardiovascular Stent - Haixin Song; Tao Wu; Xiaotian Yang; Yangzheng Li; Ye Ye; Bo Li; Tao Liu; Shihui Liu; Jianhua Li (Stem Cells International)
Late thrombosis and restenosis remain major challenges to the safety of drug-eluting stents. Biofunctional modification to endow the surface with selective anticoagulation and promote endothelium regeneration has become a hotpot recently. In this study, chitosan and heparin were found to form three-dimensional nanoparticles by spontaneous electrostatic interaction. Based on the specific binding properties between heparin and nerve growth factor (NGF), a new type of NGF-loaded heparin/chitosan nanoparticles was constructed for surface modification. The results of material characterization show that the nanoparticles are successfully immobilized on the surface of the material. In vitro blood compatibility and endothelial cell compatibility assay showed that the modified surface could selectively inhibit platelet adhesion and smooth muscle cell overproliferation, while accelerating endothelialization via promoting endothelial cell proliferation and enhancing endothelial progenitor cell mobilization.